Rola mediów w komunikacji międzynarodowej na przykładzie wydarzeń frankfurckich z 1995 r. (Politeja, 2013)
The Role of Media in International Communication as Illustrated by Events in Frankfurt in 1995The article presents results of research into the media portrayal of events in Frankfurt in 1995, as presented in local and national press in Germany and Poland. This research relied on a qualitative analysis of the text. According to the research results, German press coverage took a more balanced approach, whereas its Polish counterpart often appeared to rely more on emotional appeals based on historical events. This research complements a broader body of inquiry into the role of media in international communication, with particular emphasis on the cooperation between Polish and German journalists.